Interval algorithm for random number generation - Te Sun Hao; Hoshi, M. (IEEE transactions on information theory, 1997)
The problem of generating a random number with an arbitrary probability distribution by using a general biased M-coin is studied. An efficient and very simple algorithm based on the successive refinement of partitions of the unit interval (0, 1), which we call the interval algorithm, is proposed. A fairly tight evaluation on the efficiency is given. Generalizations of the interval algorithm to the following cases are investigated: (1) output sequence is independent and identically distributed (i.i.d.); (2) output sequence is Markov; (3) input sequence is Markov; (4) input sequence and output sequence are both subject to arbitrary stochastic processes.